Spontaneous Intracranial Hypotension associated with Posterior Reversible Encephalopathy Syndrome (Indian Journal of Case Reports, 2022)
Spontaneous Intracranial Hypotension (SIH) is usually due to cerebrospinal fluid (CSF) leak, resulting in loss of CSF volume. Posterior reversible encephalopathy syndrome (PRES) is the inability of the posterior circulation of the brain to autoregulate in response to significant variation in blood pressure. Altered perfusion with associated blood-brain barrier disruption may lead to vasogenic edema, usually without infarction, commonly in the parieto-occipital regions. Magnetic Resonance Imaging (MRI) of the brain & Spine and cerebral MR venography (MRV) are essential tools for diagnosing clinically suspected SIH and PRES. We present a case of SIH associated with PRES in an 18-year-young gentleman.